THE GEOPOLITICAL LANDSCAPE OF THE WORLD - Hojimurodova Shaxnoza Dilmurod qizi (Journals Park Publishing, 2023)
This article covered the field of geopolitics, which encompasses the most urgent issues of today's modern era, and the issue of modern trends, their characteristics, and factors affecting their formation.
Keywords: Geopolitics, science of geopolitics, history, geopolitician, Rudolph Chellen, Civilizational approach, Versailles, national interest, national development, trends, concepts, Western culture.